Abuya Drs. K.H. Saifuddin Amsir: Intelektual Ulama Betawi yang Cukup Berpengaruh Abad ke-21 - nasrullah anas nurdin (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2018)
The history of the Batavia ulama, which is actually inseparable from the history of Islam in the archipelago, turns out that the role and contribution of its ulama intellectuals is very little studied, even almost marginalized in the writing of Islamic history in Indonesia land. Therefore, a biographical review of Abuya K.H. Saifuddin Amsir (died Thursday, July 19, 2018) as a charismatic intellectual/ulama in Jakarta who was quite influential in the 21st century became very important so that religious treasure and ulama’s works as well as the historicity of Islam in Batavia can be known by the wider public. This study aims to enrich our insight into the history of Islam certain localities—in this case in the Capital City of DKI Jakarta—so as to be able to increase knowledge and appreciation to the archipelago ulama and their intellectuals who have given large role and contribution in the establishment and dynamics of Indonesian Islam.Keywords: Networking of Ulama, Betawenese, Contribution of Ulama, Scientific PublicationSejarah ulama Betawi yang sejatinya tidak bisa dipisahkan dari sejarah Islam di Nusantara, ternyata peran dan kontribusi intelektual ulamanya sangat minim ditelaah, bahkan nyaris termarginalkan dalam penulisan sejarah Islam di persada Indonesia. Karenanya, penelaahan tentang biografi Abuya K.H. Saifuddin Amsir (wafat Kamis 19 Juli 2018) selaku intelektual kharismatik/ulama Jakarta yang cukup berpengaruh pada abad ke-21 ini menjadi sangat penting agar khazanah keulamaan dan karya-karyanya sekaligus historisitas Islam di Betawi dapat dikenal oleh publik luas. Kajian ini tidak lain untuk memperkaya wawasan kita tentang sejarah Islam lokalitas tertentu—dalam hal ini di Ibukota DKI Jakarta—sehingga mampu menambah pengetahuan dan penghargaan kepada ulama Nusantara dan karya mereka, yang telah memberikan peran serta kontribusi besar dalam penguatan dan dinamika Islam Indonesia. Kata Kunci: Jaringan Ulama, Etnis Betawi, Kontribusi Ulama, Publikasi Ilmiah